Parallel Processing for Stowage Planning (I) - Han, Min Tun. (2013)
Maritime container transportation is growing significantly worldwide and container vessels are also increasing in size because of the economic scales. Ports are forced to deal with both larger container vessels and more container boxes. With respect to this evolution, container terminals are assigned an increasingly important role as key hubs within the overall transportation network. It is crucial for the container terminals to increase the efficiency of stacking and transport of the large number of containers boxes to and from the ship in order to reduce the ship turn-around time.